2009
DOI: 10.1093/brain/awp126
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia delays and alters maturation of the brain in adolescence

Abstract: Early-onset schizophrenia appears to be clinically more severe than the adult-onset form of the disease. In a previous study, we showed that anatomically related grey and white matter abnormalities found in adolescents patients were larger and more widespread than what had been reported in the literature on adult schizophrenia. Particularly, we found novel structural abnormalities in the primary sensorimotor and premotor systems. Here, we tested alternative hypotheses: either this striking sensorimotor-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
127
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(133 citation statements)
references
References 49 publications
5
127
0
1
Order By: Relevance
“…It should be noted that relatively late maturation in the lateral part of the primary motor cortex and small part of lingual gyrus is also seen during healthy adolescence and in adolescent-onset schizophrenia (38,39). We have previously found that adolescentonset schizophrenia exhibits an altered maturational pattern compared with matched healthy adolescents (38), with differences in M1, SMA, and lingual gyrus initially present at 16 y, and fading away 2.5 y later.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…It should be noted that relatively late maturation in the lateral part of the primary motor cortex and small part of lingual gyrus is also seen during healthy adolescence and in adolescent-onset schizophrenia (38,39). We have previously found that adolescentonset schizophrenia exhibits an altered maturational pattern compared with matched healthy adolescents (38), with differences in M1, SMA, and lingual gyrus initially present at 16 y, and fading away 2.5 y later.…”
Section: Discussionmentioning
confidence: 82%
“…We have previously found that adolescentonset schizophrenia exhibits an altered maturational pattern compared with matched healthy adolescents (38), with differences in M1, SMA, and lingual gyrus initially present at 16 y, and fading away 2.5 y later. One difference between the inverted-U network of IC4 and the spatial pattern of adolescent-onset schizophrenia was the absence of medial temporal lobe abnormalities in the latter case (Figs.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We adopted a longitudinal diffusion processing scheme similar to previous analyses (Douaud et al, 2009;Engvig et al, 2012). First, the initial alignment between brain-extracted images at baseline and post-treatment time points were conducted using FMRIB's Linear Image Registration Tool (FLIRT, degrees of freedom = 6), and both images were resampled to a common space halfway between the two (Jenkinson et al, 2002), which only requires a single registration per volume and thus minimizes registration bias towards one of the two time points.…”
Section: Mri Outcomes S1 Cortical Mapping With Functional Mrimentioning
confidence: 99%
“…Шизофрения, начавшаяся в раннем возрасте, является наиболее тяжелой клинической фор-мой болезни [57]. У больных с ранним началом шизофре-нии (в подростковом возрасте) методом диффузионно-тензорной томографии показаны задержка развития и со-зревания мозга и более выраженные изменения в сером и белом веществе по сравнению с началом болезни в зрелом возрасте [58], в частности нарушения сложности в форми-ровании борозд и извилин коры больших полушарий. У подростков при первом эпизоде психоза снижено со-держание N-acetyl aspartate в ПФК, отражающее сниже-ние функционального состояния нейронов, в том числе по данным магнитно-резонансной спектроскопии [59].…”
Section: рис 3 влияние возраста пациентов к периоду начала болезниunclassified